Nagwa uses cookies to ensure you get the best experience on our website. Learn more about our Privacy Policy.

Start Practicing

Worksheet: The Product Rule of Derivatives

Q1:

Find the first derivative of the function 𝑦 = π‘₯ ( 4 π‘₯ + 9 ) 4 9 at π‘₯ = βˆ’ 2 .

Q2:

Find the first derivative of the function 𝑦 = 2 π‘₯ ( 8 π‘₯ + 7 ) 5 3 at π‘₯ = βˆ’ 1 .

Q3:

Find the first derivative of the function 𝑦 = 3 π‘₯ ( 9 π‘₯ + 8 ) 5 9 at π‘₯ = βˆ’ 1 .

Q4:

Find the first derivative of the function 𝑦 = 2 π‘₯ 𝑒 8 5 π‘₯ .

  • A 1 6 π‘₯ 𝑒 + 2 π‘₯ 𝑒 7 5 π‘₯ 8 5 π‘₯
  • B 1 6 π‘₯ 𝑒 βˆ’ 1 0 π‘₯ 𝑒 7 5 π‘₯ 8 5 π‘₯
  • C 2 π‘₯ 𝑒 + 2 π‘₯ 𝑒 7 5 π‘₯ 8 5 π‘₯
  • D 1 6 π‘₯ 𝑒 + 1 0 π‘₯ 𝑒 7 5 π‘₯ 8 5 π‘₯
  • E 8 0 π‘₯ 𝑒 7 5 π‘₯

Q5:

Given that d d π‘₯ 𝑒 = π‘˜ 𝑒 π‘˜ π‘₯ π‘˜ π‘₯ , find π‘˜ so that 𝑔 ( π‘₯ ) = π‘₯ 𝑒 2 π‘˜ π‘₯ satisfies 𝑔 β€² ( 1 ) = 0 .

Q6:

Find the first derivative of the function 𝑓 ( π‘₯ ) = ο€Ή 2 π‘₯ + π‘₯ βˆ’ 5  ο€Ό π‘₯ + 3 √ π‘₯ βˆ’ 3 π‘₯  4 2 .

  • A 8 π‘₯ + 2 7 √ π‘₯ βˆ’ 1 8 π‘₯ βˆ’ 1 5 π‘₯ + π‘₯ βˆ’ 1 5 √ π‘₯ 5 7 4 2 2 5
  • B 8 π‘₯ + 2 7 √ π‘₯ βˆ’ 1 8 π‘₯ βˆ’ 1 5 π‘₯ + π‘₯ βˆ’ 1 5 √ π‘₯ 4 5 3 3
  • C 8 π‘₯ + 2 7 √ π‘₯ βˆ’ 1 8 π‘₯ βˆ’ 1 5 π‘₯ + π‘₯ βˆ’ 1 5 √ π‘₯ 5 9 4 3 3 7
  • D 1 2 π‘₯ + 2 7 π‘₯ √ π‘₯ βˆ’ 1 5 π‘₯ + 9 2 √ π‘₯ βˆ’ 1 0 π‘₯ βˆ’ 1 5 2 √ π‘₯ βˆ’ 1 5 π‘₯ 5 3 2 2

Q7:

Let 𝑔 ( π‘₯ ) = βˆ’ 3 𝑓 ( π‘₯ ) [ β„Ž ( π‘₯ ) βˆ’ 1 ] . If 𝑓 β€² ( βˆ’ 4 ) = βˆ’ 1 , β„Ž β€² ( βˆ’ 4 ) = βˆ’ 9 , β„Ž ( βˆ’ 4 ) = βˆ’ 6 , and 𝑓 ( βˆ’ 4 ) = βˆ’ 1 , find 𝑔 β€² ( βˆ’ 4 ) .

Q8:

Find d d 𝑦 π‘₯ at π‘₯ = 2 when 𝑦 = ο€Ή π‘₯ + π‘₯ βˆ’ 2  ο€Ή βˆ’ 3 π‘₯ + 7 π‘₯ βˆ’ 1  2 2 2 5 .

Q9:

Find d d 𝑦 π‘₯ if 𝑦 = 𝑒 π‘Ž 2 π‘₯ 3 π‘₯ + 8 2 .

  • A 𝑒 π‘Ž ( 1 + 6 π‘₯ π‘Ž ) 2 π‘₯ 3 π‘₯ + 8 2 l n
  • B 𝑒 π‘Ž ( 2 + π‘Ž ) 2 π‘₯ 3 π‘₯ + 8 2 l n
  • C 𝑒 π‘Ž ( 1 + π‘Ž ) 2 π‘₯ 3 π‘₯ + 8 2 l n
  • D 2 𝑒 π‘Ž ( 1 + 3 π‘₯ π‘Ž ) 2 π‘₯ 3 π‘₯ + 8 2 l n

Q10:

Suppose that 𝑓 is differentiable. What is the derivative of π‘₯ 𝑓 ( π‘₯ ) 3 ?

  • A π‘₯ 𝑓 ( π‘₯ ) + π‘₯ 𝑓 β€² ( π‘₯ ) 2 3
  • B 3 π‘₯ 𝑓 β€² ( π‘₯ ) 2
  • C π‘₯ 𝑓 β€² ( π‘₯ ) 2
  • D 3 π‘₯ 𝑓 ( π‘₯ ) + π‘₯ 𝑓 β€² ( π‘₯ ) 2 3
  • E 3 π‘₯ + 𝑓 β€² ( π‘₯ ) 2

Q11:

The product rule says that ( 𝑓 𝑔 ) = 𝑓 𝑔 + 𝑓 𝑔 β€² β€² β€² . Use this to derive a formula for the derivative ( 𝑓 𝑔 β„Ž ) β€² .

  • A 𝑓 𝑔 β„Ž βˆ’ 𝑓 𝑔 β„Ž βˆ’ 𝑓 𝑔 β„Ž β€² β€² β€²
  • B 𝑓 𝑔 β„Ž + 𝑓 𝑔 β„Ž β€² β€² β€²
  • C 𝑓 𝑔 β„Ž + 𝑓 𝑔 β„Ž β€² β€²
  • D 𝑓 𝑔 β„Ž + 𝑓 𝑔 β„Ž + 𝑓 𝑔 β„Ž β€² β€² β€²
  • E 𝑓 𝑔 β„Ž + 𝑓 𝑔 β„Ž + 𝑓 𝑔 β„Ž β€² β€²

Q12:

Using the product rule, find d d π‘₯ ( π‘₯ 𝑒 ) 2 βˆ’ π‘₯ .

  • A π‘₯ 𝑒 βˆ’ π‘₯ 𝑒 βˆ’ π‘₯ 2 βˆ’ π‘₯
  • B 2 π‘₯ 𝑒 + π‘₯ 𝑒 βˆ’ π‘₯ 2 βˆ’ π‘₯
  • C π‘₯ 𝑒 + π‘₯ 𝑒 βˆ’ π‘₯ 2 βˆ’ π‘₯
  • D 2 π‘₯ 𝑒 βˆ’ π‘₯ 𝑒 βˆ’ π‘₯ 2 βˆ’ π‘₯
  • E 2 π‘₯ 𝑒 βˆ’ π‘₯ 𝑒 2 βˆ’ π‘₯ 2 βˆ’ π‘₯

Q13:

Suppose that 𝑓 ( 2 ) = 3 , 𝑔 ( 2 ) = 5 , 𝑓 β€² ( 2 ) = βˆ’ 1 , and 𝑔 β€² ( 2 ) = 6 . Evaluate ( 𝑓 ( π‘₯ ) 𝑔 ( π‘₯ ) ) β€² βˆ’ 𝑓 β€² ( π‘₯ ) 𝑔 β€² ( π‘₯ ) at π‘₯ = 2 .

Q14:

Find the first derivative of 𝑦 = ( π‘₯ βˆ’ 5 ) ( π‘₯ βˆ’ 2 ) 6 at ( 1 , βˆ’ 4 ) .

Q15:

Find the first derivative of 𝑓 ( π‘₯ ) = ο€Ή 9 π‘₯ βˆ’ π‘₯ βˆ’ 7  ο€Ή 7 π‘₯ βˆ’ 8 π‘₯ βˆ’ 7  2 2 at ( βˆ’ 1 , 2 4 ) .

Q16:

Find the first derivative of 𝑓 ( π‘₯ ) = ο€Ή 5 π‘₯ + 3 π‘₯ βˆ’ 1  ο€Ή 9 π‘₯ + 5 π‘₯ + 2  2 2 at ( βˆ’ 1 , 6 ) .

Q17:

Find the first derivative of 𝑓 ( π‘₯ ) = ο€Ή 2 π‘₯ βˆ’ 5 π‘₯ βˆ’ 3  ο€Ή 5 π‘₯ βˆ’ π‘₯ + 2  2 2 at ( 0 , βˆ’ 6 ) .

Q18:

Given 𝑦 𝑦 = βˆ’ 6 𝑒 ο€Ή βˆ’ π‘₯ + 3  : l n 4 π‘₯ 2 , determine d d 𝑦 π‘₯ .

  • A βˆ’ 6 𝑒  2 π‘₯ π‘₯ βˆ’ 3 + ο€Ή βˆ’ π‘₯ + 3   4 π‘₯ 2 2 l n
  • B βˆ’ 4 8 𝑒 π‘₯ π‘₯ βˆ’ 3 4 π‘₯ 2
  • C βˆ’ 6 𝑒  βˆ’ 2 π‘₯ π‘₯ βˆ’ 3 + 4 ο€Ή βˆ’ π‘₯ + 3   4 π‘₯ 2 2 l n
  • D βˆ’ 6 𝑒  2 π‘₯ π‘₯ βˆ’ 3 + 4 ο€Ή βˆ’ π‘₯ + 3   4 π‘₯ 2 2 l n

Q19:

Determine the derivative of 𝑦 = 𝑒 π‘₯ βˆ’ 5 π‘₯ 2 .

  • A 𝑦 β€² = 𝑒 π‘₯ ( π‘₯ + 2 ) βˆ’ 5 π‘₯
  • B 𝑦 β€² = 𝑒 π‘₯ ( 5 π‘₯ + 2 ) βˆ’ 5 π‘₯
  • C 𝑦 β€² = βˆ’ 𝑒 π‘₯ ( 5 π‘₯ βˆ’ 1 ) βˆ’ 5 π‘₯
  • D 𝑦 β€² = βˆ’ 𝑒 π‘₯ ( 5 π‘₯ βˆ’ 2 ) βˆ’ 5 π‘₯
  • E 𝑦 β€² = βˆ’ 3 𝑒 π‘₯ βˆ’ 5 π‘₯ 2

Q20:

Find the first derivative of 𝑓 ( π‘₯ ) = 2 π‘₯ ( π‘₯ βˆ’ 3 ) ( π‘₯ βˆ’ 1 ) ( π‘₯ + 2 ) at ( βˆ’ 1 , βˆ’ 1 6 ) .

Q21:

Find the first derivative of 𝑓 ( π‘₯ ) = π‘₯ ( π‘₯ βˆ’ 1 ) ( π‘₯ + 4 ) ( π‘₯ + 6 ) at ( βˆ’ 5 , βˆ’ 3 0 ) .

Q22:

If π‘₯ = 3 𝑦 𝑒 7 9 √ 𝑦 , find d d π‘₯ 𝑦 .

  • A 3 𝑦 𝑒 ο€Ό 9 2 √ 𝑦 + 1  6 9 √ 𝑦
  • B 2 1 𝑦 ο€Ό 9 1 4 √ 𝑦 + 1  6
  • C 3 𝑦 𝑒 ο€Ό 9 7 √ 𝑦 + 1  6 9 √ 𝑦
  • D 2 1 𝑦 𝑒 ο€Ό 9 1 4 √ 𝑦 + 1  6 9 √ 𝑦

Q23:

Given 𝑦 = 8 𝑒 9 π‘₯ + 3 π‘₯ 7 π‘₯ 3 l n , find d d 𝑦 π‘₯ .

  • A 8 𝑒 9 π‘₯ + 8 π‘₯ 𝑒 + 3 π‘₯ 7 π‘₯ 7 π‘₯ 2 l n
  • B 5 6 𝑒 9 π‘₯ + 8 𝑒 9 π‘₯ + 9 π‘₯ 7 π‘₯ 7 π‘₯ 2 l n
  • C 8 π‘₯ 𝑒 + 9 π‘₯ + 5 6 9 π‘₯ 7 π‘₯ 2 l n
  • D 5 6 𝑒 9 π‘₯ + 8 π‘₯ 𝑒 + 9 π‘₯ 7 π‘₯ 7 π‘₯ 2 l n

Q24:

Differentiate 𝑇 ( 𝑧 ) = 7 4 𝑧 𝑧 7 l o g .

  • A 𝑇 β€² ( 𝑧 ) = 7 ο€Ό 4 𝑧 + 1 𝑧 7  𝑧 7 l o g l n
  • B 𝑇 β€² ( 𝑧 ) = 7 𝑧 7 𝑧 l n
  • C 𝑇 β€² ( 𝑧 ) = 7 ο€Ό 4 𝑧 βˆ’ 1 𝑧 7  𝑧 l n l n
  • D 𝑇 β€² ( 𝑧 ) = 7 ο€Ό 4 𝑧 + 1 𝑧 7  𝑧 l n l n
  • E 𝑇 β€² ( 𝑧 ) = 7 ο€Ό 4 𝑧 βˆ’ 1 𝑧 7  𝑧 7 l o g l n

Q25:

Find the first derivative of 𝑓 ( π‘₯ ) = ο€Ή π‘₯ + 4  ο€Ί 3 π‘₯ √ π‘₯ βˆ’ 7  ο€Ί 3 π‘₯ √ π‘₯ + 7  8 at π‘₯ = βˆ’ 1 .